Levels of oxidative stress in patients with neoadjuvant chemotherapy for gastric cancer: correlation with treatment response - Lu, Jiatong; Guan, Shaoyu; Luo, Jiajun; Yuan, Jingwen; Yan, Junfeng; Yang, Chen; Tong, Qiang (Frontiers in Oncology, 2023)
Objective The intent of this study was to investigate the relationship between oxidative stress and treatment response in gastric cancer patients undergoing neoadjuvant chemotherapy. Methods Blood samples from 108 patients and 108 healthy subjects were collected, and all patients were enrolled in SOX chemotherapy. The patients received four cycles of neoadjuvant chemotherapy. Blood samples were collected to determine oxidative stress levels at baseline prior to beginning chemotherapy, and at the end of cycles 2 and 4. The patients receiving neoadjuvant chemotherapy were followed up for several months to years. A survival curve was created according to the follow-up information from the patients. In addition, the correlation between oxidative stress level and treatment effect was evaluated and ROC curves were plotted according to the final collected data. Results Compared with the normal group, the levels of the antioxidant index decreased while the peroxide index increased in the patients. Conversely, when patients were compared before and after chemotherapy, the antioxidant index increased but the peroxide index decreased. Furthermore, the antioxidant index increased in the response group while the peroxide index decreased in the non-response group. Conclusion Patients with an increased antioxidant index after chemotherapy have good treatment responsiveness. These indicators can also be used as predictors to judge the patients’ response to chemotherapy.